A one shot method for divertor target shape optimization. Issue 1 (December 2014) - Dekeyser, Wouter; Reiter, Detlev; Baelmans, Martine
Abstract Shape optimization methods, as commonly applied in aerodynamic design applications, have recently been adapted for use in nuclear fusion divertor target design. The resulting algorithms are very efficient compared to the standard use of numerical edge plasma simulations as analysis tools only. In this paper, we highlight some numerical aspects of the underlying algorithm, focusing on a correct, nine‐point discretization of the fluxes and the need for an adjoint pressure correction equation. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)